2021
DOI: 10.21203/rs.3.rs-824447/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of Hsa-miR-3616-3p in Triple-Negative Breast Cancer is Associated with Cell Migration and Invasion

Abstract: Background: Micro RNA (miRNA), a class of endogenous small RNAs with a length of about 20-24 nucleotides, have been played a variety of important regulatory roles in cells and have attracted the attention of researchers because involvement of initiation and progression of diverse kinds of human diseases, especially cancer. However, the regulatory role of miRNA in triple negative breast cancer (TNBC), its clinical significance and potential mechanism are still largely unknown.Methods: In this study, the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Similar to our study, Lu et al also pointed out that has-mir-3614 is low-expressed in endometrial cancerous tissue [53]. A previous study had showed that the low-expression of has-mir-3616 contributes to triple negative breast cancer migration and invasion [54], and at the same time, low-expression of hsamir-3616 was also found to significantly reduce the survival rate of EC patients in this study (p < 0.001), which may be related to the expression of target mRNA. Translational inhibition or destabilization causes immunosuppression that forms the tumor microenvironment, and this can further be explored as potential targets of EC-related miRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study, Lu et al also pointed out that has-mir-3614 is low-expressed in endometrial cancerous tissue [53]. A previous study had showed that the low-expression of has-mir-3616 contributes to triple negative breast cancer migration and invasion [54], and at the same time, low-expression of hsamir-3616 was also found to significantly reduce the survival rate of EC patients in this study (p < 0.001), which may be related to the expression of target mRNA. Translational inhibition or destabilization causes immunosuppression that forms the tumor microenvironment, and this can further be explored as potential targets of EC-related miRNAs.…”
Section: Discussionsupporting
confidence: 90%